The Score Family Assessment Questionnaire: A Decade of Progress. Issue 2 (15th February 2017) - Carr, Alan; Stratton, Peter
Abstract : This paper reviews a decade of research (2006–2016) on a family assessment instrument called the Systemic Clinical Outcome and Routine Evaluation (SCORE). The SCORE was developed in Europe to monitor progress and outcome in systemic therapy and has been adopted by the European Family Therapy Association as the main instrument for assessing the outcome in systemic family and couple therapy. There are currently six main versions of this instrument: SCORE‐40, SCORE‐15, SCORE‐28, SCORE‐29, Child SCORE‐15, and Relational SCORE‐15. It has also been translated into a number of European languages. Fifteen empirical studies of the SCORE "family of measures" have been conducted. Most have aimed to establish psychometric properties of these instruments in English and other languages. Others have used the SCORE to document the level of family adjustment in clinical samples or evaluate outcome in treatment trials. There is now sufficient evidence for the reliability and validity of the SCORE to justify the use of brief versions of this instrument to monitor progress and outcome in the routine practice of systemic therapy. Abstract : Video Abstract